Study of acetaminophen (paracetamol) effect in the embryonic development of the Swiss Albino mouse Mus musculus - Hani Hamoudi (مجلة التربية والعلم, 2005)
The present study has conducted to investigate the effect of acetaminophen (paracetamol) on embryonic developmental in swiss albino mice Mus musculm , morphologically and histologically by light microscope, by giving the pregnant mice doses of 20, 50 ml/kg acetaminophen, The results is showed the normal period of pregnancy and this pregnancy did not happen at the fixed period, when compared to the controlled group which continued 18 days, where as it continued 19 days in the first group, which was treated with 20 ml/kg acetaminophen, as for the third group which was given a dose of 50 ml/kg acetaminophen, it lasted 20 days. The study showed abnormal embryonic differentiation in the group given a highly concentrated dose 50 ml/kg compared with ihe other two groups which were given a low concentration dose 20 im/kg. The histological test led to necrosis in liver, in addition to that necrosis appears in spinal cord and cavities of the brain in (lie high concentrated dose group compared with the low concentrated group dose which showed some histopathological changes such as vacillation in diencephalen and some necrosis in the liver when compared to two groups with the controlled group.